Street-Level Workers and the Temporalities of Waiting in the Italian Asylum System - Pasian, Pamela (Italian Sociological Review, 2024)
Immigration and asylum have become enormously contested in Italy over recent decades. Weak planning capacities and logics of emergency have typically permeated Italian policymaking on migration and, even more so, on asylum. Currently the Italian reception system implements a widespread framework managed by public authorities. It is characterized by policies of subsidiarity where different actors, public and private, are involved at various levels of government. Generally, public authorities subcontract third sector actors and NGOs to provide inclusion and integration services. The role of these agents is the focus of this article, particularly how they use their discretionary power to cope with the task of implementing a state mandate concerning the management of the condition of immobility that affects the temporality of refugees and asylum seekers, while waiting to obtain a permit or social and labour inclusion processes. Drawing on ethnographic research realized in the realm of the project “SIforREF - Integrating Refugees in Society and Labour Market through Social Innovation”, founded by the Interreg Central Europe Program, this contribution shows how street-level workers use their discretionary power as a tactic that promotes their value and beliefs.